PEMAHAMAN NILAI-NILAI SYARIâAH TERHADAP PERILAKU BERDAGANG (Studi pada Pedagang di Pasar Bambu Kuning Bandar Lampung) - Zakiyah, Zakiyah (SOCIOLOGIE, 2013)
This research intends to describe the sharia values comprehension towards bargain behaviour amid Bambu Kuning Market merchants in Bandar Lampung. The type of this research is qualitative research along with observation, documentation, and in dept interview as the data collecting method. Data analysis technique is done by the way data reduction, data presentation, and conclusion. Based on research output, it can be concluded that merchantâs comprehension toward sharia values and their bargain behaviour have quite diverse comprehension and behaviour. Diverse points of view which are related to trade in the eyes of Islam, with diverse comprehension and behaviour are shown by Bambu Kuning merchants in Bandar Lampung. Bargain within religion is allowed, even it is something recommended. However, bargain has to pay attention rules be appointed by Islam religion. Merchantâs sharia value comprehension becomes the basic to act and behave for them suit Islamic bargain etiquette or values. For example, Islamic principle encourages the merchants being truthful, mandate, and genuine as the fundamental for them do not lie setting the prices and truthful in weighing. Whereupon, based on research output, there are some frauds of merchantâs behaviour from sharia values in bargaining. Other examples are setting higher prices too far than early price, and cheating in weighing mainly by the fruit merchants. That behaviour is one of deviation towards Islam religion guideline. Further, sharia values relating to Islamic bargain etiquette are shown by merchants on their everyday bargain practice.Keywords: Sharia values, trading